Revisiting the Kπ puzzle in the pQCD factorization approach - 白玮 刘敏 樊莹莹 王文飞 程山 肖振军 (Chinese physics C, 2014)
In this paper,we calculated the branching ratios and direct CP violation of the four B→Kπ decays with the inclusion of all currently known next-to-leading order（NLO） contributions by employing the perturbative QCD（pQCD） factorization approach.We found that（a） Besides the 10%enhancement from the NLO vertex corrections,the quark-loops and magnetic penguins,the NLO contributions to the form factors can provide an additional~15%enhancement to the branching ratios,and lead to a very good agreement with the data;（b） The NLO pQCD predictions are A_（CP）~（dir）（B~0→K~＋π~0）=（-6.5±3.1）%and A_（CP）~（dir）（B~＋→K~＋π~0）=（2.2±2.0）%,become well consistent with the data due to the inclusion of the NLO contributions.